The Final Degree Project in Technical Architecture: Evolution and contents - González Moreno, Sara; Zurro García, Belén; González Martín, José Manuel; Bernal López-Sanvicente, Amparo; Rodríguez Saiz, Ángel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
One of the most important components of the teaching-learning process of the Technical Architecture degree is the completion of the BA dissertation that combines all the knowledge and skills developed in the different disciplines that make up the Study Plan. The aim of this paper is to visualize the evolution of the teaching and learning process in the Final Degree Project in the Technical Architecture and Building Engineering studies of Burgos University, showing the different adaptations of the contents and the typology chosen for its development.